Statistical Analysis of the Government Expenditure for Greece: January 2008- September 2015 - Duzha, Juxhen; Hoxhalli, Brunilda; Lika, Enxhi; Mici, Steisi (European Journal of Economics and Business Studies, 2016)
The main purpose of the present study is to develop a statistical analysis of the government expenditure for Greece during the period January 2008- September 2015. The source of the official data is the Greece Organization for Economic Co-operation and Development. The Kolmogorov’s Central Limit Theorem, “fair game” concept in the sense of Stein-Vorobiev, Kolmogorov- Smirnov- Lilliefors test and Shapiro- Wilk test are applied. The government expenditure is estimated based on current price or as a percentage of GDP. Some results of the present study include: The official data of quarterly government expenditure for Greece during the period January 2008-September 2015 contradicts the CLT at the confidence level 95 percent. The official data of quarterly government expenditure expressed as a fraction of GDP for Greece during the period January 2008-September 2015 contradicts CLT at the confidence level 95 percent. The government expenditure process in Greece during the period January 2008-September 2015 is an unfair game at the confidence level 95 percent. The government expenditure as a fraction of GDP in Greece during the period January 2008-September 2015 is an unfair game at the confidence level 95 percent. The official data of quarterly GDP for Greece during the specified period contradicts CLT at the confidence level 95 percent. The quarterly GDP in Greece during the specified period is a fair game at the confidence level 95 percent.
Keywords: government expenditure, GDP, CLT, fair game, OECD, Greece